Friedrich Wilhelm Tobias Hunger (1874–1952). Biograaf van botanische helden en ‘anti-vaderlander’ - van Gelder, Esther (Studium, 2013)
Friedrich Wilhelm Tobias Hunger (1874–1952). Biograaf van botanische helden en ‘anti-vaderlander’